Flexible three-scale super-hydrophobic surface and preparation method thereof
By setting up a multi-level scale structure on the substrate surface to form a flexible three-scale superhydrophobic surface, the problem that water droplets are prone to change to a high adhesion state in the prior art is solved, and the effect of delaying icing and reducing ice adhesion strength is achieved.
Patent Information
- Application Number
- CN202510172889.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-08
AI Technical Summary
The existing superhydrophobic surface cannot completely prevent icing, and water droplets tend to turn into a high adhesion state on the surface, resulting in an increase in the icing rate and ice adhesion strength.
By providing a multi-level scale structure on the substrate surface, including a first-level scale raised structure, a second-level scale raised structure and a third-level scale groove structure, a flexible three-scale superhydrophobic surface is formed, and the size of each scale structure is limited to improve the roughness and hydrophobicity of the surface.
The water droplets are realized in the Cassie-Baxter state on the surface, which reduces the adhesion and icing rate of the water droplets, delays the icing process, and reduces the adhesion strength of the ice layer.
Smart Images

Figure CN119775614A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of super-hydrophobic materials, and in particular relates to a flexible three-scale super-hydrophobic surface and a preparation method thereof. Background Art
[0002] Among the many anti-icing technologies, mechanical and thermal deicing are typical active deicing technologies. The technology is relatively mature, but it requires the installation of additional deicing equipment and will also bring high energy consumption. Therefore, the development of passive anti-icing technology based on material surface properties has received attention from the industry. Superhydrophobic materials have shown great potential in many aspects such as water repellent adhesion, delayed icing, and reduced ice adhesion. In particular, the flexible superhydrophobic surface based on polymer substrates has a wider range of application scenarios and is more suitable for configuration in complex structural parts such as engines, wing fronts, and wind turbine blades. The flexible characteristics of the substrate and the synergistic effect of the surface microstructure can also effectively enhance the superhydrophobic properties of the material.
[0003] However, existing super-hydrophobic surfaces cannot completely prevent ice formation, but can only inhibit ice formation to a certain extent. Water droplets on super-hydrophobic surfaces are usually in a spherical Cassie wetting state. The low-adhesion Cassie state is a metastable state. When the droplets are subjected to external loads such as rapid cooling, high-frequency vibration, and impact, the droplets are easily transformed into a high-adhesion Wenzel state, which significantly increases the freezing rate and ice adhesion strength. Summary of the invention
[0004] The purpose of this application is to provide a flexible three-scale super-hydrophobic surface and a preparation method thereof to solve the above-mentioned technical problems existing in the prior art.
[0005] This application is implemented as follows: In the first aspect, an embodiment of the present application provides a flexible three-scale super-hydrophobic surface, including a substrate, which is a flexible structure, and the surface of the substrate is provided with a plurality of uniformly distributed first-level scale structures, a plurality of uniformly distributed second-level scale structures, and a plurality of third-level scale structures. The first-level scale structure and the second-level scale structure are protrusion structures, and the width dimension of the first-level scale structure is between 60 microns and 140 microns, and the width dimension of the second-level scale structure is between 10 microns and 15 microns. The third-level scale structure is a groove structure, and the width dimension of the third-level scale structure is between 50 nanometers and 100 nanometers. The first-level scale structure surface and the second-level scale structure surface are both provided with the third-level scale structure.
[0006] In the second aspect, the embodiment of the present application provides a method for preparing a flexible three-scale super-hydrophobic surface, which is used to prepare the flexible three-scale super-hydrophobic surface provided by the embodiment of the first aspect, and the specific preparation steps are as follows: processing a first-level scale groove structure and a second-level scale groove structure on a metal template; pouring a PDMS material on the metal template, and after the PDMS material is solidified, removing the PDMS material from the metal template to obtain a two-scale structure sample having a first-level scale structure and a second-level scale structure; processing a third-level scale structure on the surface of the two-scale structure sample to obtain a flexible three-scale super-hydrophobic surface.
[0007] The technical solution adopted by the present invention can achieve the following beneficial effects: In the present application, a three-scale surface is formed by arranging a first-level scale structure, a second-level scale structure and a third-level scale structure on the surface of a substrate, and by limiting the size of each scale structure, the micro-nano structure on the surface of the substrate is enriched, the roughness of the surface of the substrate is increased, thereby increasing the contact angle and hydrophobicity of the surface of the substrate, and water droplets present a Cassie-Baxter state on the surface of the substrate; the rich micro-nano structure on the surface of the substrate has low adhesion characteristics for water droplets, and water droplets will rebound after falling onto the surface of the substrate, thereby avoiding or reducing the occurrence of water droplets adhering to the surface of the substrate; in addition, since the contact angle of the surface of the substrate is large, the large contact angle reduces the contact area between the droplet and the surface, and a large number of bubbles are interspersed between the droplet and the three-scale micro-nano structure on the surface of the substrate, further preventing heat transfer, thereby achieving the effect of delayed freezing; even if the water droplets freeze on the surface of the substrate, due to the large contact angle, the micro-nano structure on the surface of the substrate is filled with a large amount of air, making the ice layer easier to fall off, thereby reducing the ice adhesion strength of the substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0009] Figure 1 It is a schematic diagram of the preparation process of a flexible three-scale super-hydrophobic surface provided in some embodiments of the present application; Figure 2 is a schematic diagram of the structure of Al-60 provided in some embodiments of the present application; Figure 3 is a schematic diagram of the structure of Al-80 provided in some embodiments of the present application; Figure 4 is a schematic diagram of the structure of Al-100 provided in some embodiments of the present application; Figure 5 is a schematic diagram of the structure of Al-120 provided in some embodiments of the present application; Figure 6 is a schematic diagram of the structure of Al-140 provided in some embodiments of the present application; Figure 7 is a schematic diagram of the structure of a two-scale structure sample provided in some embodiments of the present application; Figure 8 It is a schematic diagram of the structures of T-0, T-60, T-80, T-100, T-120 and T-140 provided in some embodiments of the present application; Fig. 9 These are the test results of wettability test on T-0, T-60, T-80, T-100, T-120 and T-140; Fig.10 These are the experimental results of droplet impact experiments on T-0, T-60, T-80, T-100, T-120, and T-140; Fig.11 These are the experimental results of droplet freezing experiments on T-0, T-60, T-80, T-100, T-120, and T-140; Fig.12 It is the test result of ice strength adhesion test on D-0, D-60, D-80, D-100, D-120, D-140, T-0, T-60, T-80, T-100, T-120, T-140; Fig.13 These are the test results of ice strength adhesion test on D-0, D-60, D-80, D-100, D-120, D-140, T-0, T-60, T-80, T-100, T-120, and T-140 at a wind speed of 5m / s. DETAILED DESCRIPTION
[0010] The following description provides many different embodiments or examples for implementing different features of the present invention. The components and arrangements described in the following specific examples are only used to simplify the present invention and are only used as examples, not to limit the present invention.
[0011] The embodiment of the present application provides a flexible three-scale super-hydrophobic surface, including a substrate, which is a flexible structure. The flexible structure has a wider range of usage scenarios and is more suitable for configuration in complex parts such as engines, wing front edges, and wind turbine blades. The substrate surface is provided with a three-scale micro-nano structure, specifically including a first-level scale structure, a second-level scale structure, and a third-level scale structure. The first-level scale structure and the second-level scale structure are convex structures, and the third-level scale structure is a groove structure.
[0012] There are multiple first-level scale structures, which are evenly distributed on the substrate surface. The first-level scale is generally a sub-millimeter scale, that is, about 100 microns. In some embodiments of the present application, the width of the first-level scale structure is between 60 microns and 140 microns.
[0013] There are multiple second-level scale structures, which are evenly distributed on the surface of the substrate. The second-level scale is generally micrometer-scale. In some embodiments of the present application, the width of the second-level scale structure is between 10 micrometers and 15 micrometers.
[0014] There are also multiple third-level scale structures, and the first-level scale structure surface and the second-level scale structure surface are both provided with third-level scale structures, and the third-level scale structures are generally nanometer-scale. In some embodiments of the present application, the width of the third-level scale structure is between 50 nanometers and 100 nanometers.
[0015] The three-scale structures enrich the micro-nano structure of the substrate surface and increase the roughness of the substrate surface. The contact angle of the substrate surface is larger, which improves the hydrophobicity of the substrate surface and reaches the super-hydrophobic level. The water droplets on the surface show a Cassie-Baxter state. The water droplets are partially supported by the rough structure of the substrate surface and partially surrounded by air, forming a liquid-solid and liquid-gas composite interface. In this state, the actual contact area between the droplets and the substrate surface is small, and the droplets can easily roll off the solid surface.
[0016] The rich micro-nano structures on the substrate surface have low adhesion properties for water droplets. After the water droplets fall on the substrate surface, they will bounce back, thereby reducing or even avoiding the situation where the water droplets adhere to the substrate surface. In some embodiments, when the width of the scale structure is appropriate, the water droplets may even bounce off the substrate surface and then jump up again.
[0017] Moreover, due to the large contact angle of the substrate surface, the contact area between the droplet and the substrate surface is small, and a large number of bubbles are sandwiched between the droplet and the three-scale micro-nano structure of the surface, which further slows down the heat transfer and further prevents the heat transfer, thereby achieving the effect of delayed freezing.
[0018] In addition, as the contact angle increases, the ice on the substrate surface is Cassie ice. The micro-nanostructure on the substrate surface is filled with a large amount of air. The interaction force between the ice layer and the substrate surface is weak, and the ice layer is easier to fall off, thereby reducing the ice adhesion strength of the substrate.
[0019] Some embodiments of the present application also provide a method for preparing a flexible three-dimensional super-hydrophobic surface, which is used to prepare the flexible three-dimensional super-hydrophobic surface provided in the above embodiments. The preparation steps can be referred to Figure 1 As shown, the specific preparation steps are as follows: A first-level scale groove structure and a second-level scale groove structure are processed on the metal template.
[0020] The PDMS material is poured on the metal template, and after the PDMS material is solidified, the PDMS material is removed from the metal template to obtain a two-scale structure sample with a first-level scale structure and a second-level scale structure. The PDMS material is filled in the first-level scale groove structure and the second-level scale groove structure, and after the PDMS material is solidified and removed from the metal template, the PDMS material located in the first-level scale groove structure and the second-level scale groove structure forms the first-level scale structure and the second-level scale structure, completing the transfer to the metal template.
[0021] The metal template is easier to process the first-level scale groove structure and the second-level scale groove structure, has higher processing accuracy, and uses PDMS material for transfer to obtain a flexible substrate for easy use.
[0022] After obtaining the two-scale structure sample, the third-level scale structure is processed on the surface of the two-scale structure sample to obtain a flexible three-scale super-hydrophobic surface. The third-level scale structure is small in size and difficult to transfer. Direct processing on the surface of the two-scale structure sample can reduce the processing difficulty. In addition, the groove structure formed by direct processing is significantly different from the protrusion of the first-level scale structure, further enriching the micro-nano structure of the substrate surface.
[0023] The first-level scale groove structure, the second-level scale groove structure, and the third-level scale structure are all processed by femtosecond laser processing. According to the different sizes of the three scales, the specific processing methods are also different. For the first-level scale groove structure with a larger scale, the laser circle sweeping processing method is adopted. For the second-level scale groove structure, the laser pulse dotting processing method is adopted, and the third-level scale structure is processed by laser sweeping line processing.
[0024] In some preferred embodiments, the first-level scale groove structure is a rectangular micro-pit, the first-level scale structure is a rectangular protrusion, the second-level scale groove structure is a circular micro-pit, and the second-level scale structure is a circular protrusion. In some specific embodiments, when a femtosecond laser processing method is used, for the first-level scale groove structure, the rectangular micro-pit array processing power is 260mW, the scanning line spacing is 0.054mm, and the scanning line speed is 0.01m / s. For the second-level scale groove structure, the circular micro-pit array is laser pulse dot processing, the power is 20mW, and the single point exposure time is 20000 .
[0025] When processing the metal template, the first-level scale groove structure and the second-level scale groove structure do not interfere with each other. The second-level scale groove structure may be located on the metal template surface outside the first-level scale groove structure, or it may be directly located inside the first-level scale groove structure. Due to the size difference between the two scale structures, even if femtosecond laser processing is used, the specific processing methods used are different.
[0026] For the first-level groove structure with a larger structural scale, that is, the rectangular micro-pit, after multiple scans with the same power, the rectangular micro-pit array size is consistent, and the molten material is less accumulated. However, for the second-level groove structure, that is, the circular micro-pit, if the same processing method is used, there will be large size deviations and more molten material accumulation. The main reason is that the laser spot itself has a diameter. Even if the power is reduced, the spot diameter will interfere with the structural size, affecting the dimensional accuracy, and the processing time will be greatly extended. Therefore, the laser processing method was changed from laser circle scanning to laser pulse dotting. After multiple dotting, the circular micro-pits have high dimensional accuracy and less molten material accumulation at the pit edge.
[0027] In addition, it should be noted that the distance between two adjacent circular micro-pits should not be too large, which is consistent with the scale of the second-level scale structure. The distance between two adjacent circular micro-pits is between 10 microns and 15 microns. After transferring the metal template, the distance between two adjacent second-level scale structures of the obtained two-scale structure sample or flexible three-scale superhydrophobic surface is between 10 microns and 15 microns.
[0028] The distance between two adjacent rectangular micro-pits should not be too large, generally between 10 microns and 30 microns. After the metal template is transferred, the distance between two adjacent first-level scale structures is between 10 microns and 30 microns.
[0029] When processing the metal template, it is necessary to pay attention not only to the radial size of the rectangular micro-pits and the circular micro-pits, but also to the depth of the micro-pits. In some embodiments of the present application, the depth of the rectangular micro-pits is between 80 microns and 100 microns, and the height of the first-level scale structure obtained after the transfer of the metal template is between 80 microns and 100 microns; the depth of the circular micro-pits is between 12 microns and 18 microns, and the height of the second-level scale structure obtained after the transfer of the metal template is between 12 microns and 18 microns.
[0030] In some embodiments, all third-level scale structures on the substrate are divided into multiple groups of groove groups arranged along the first direction, and each group of groove groups includes multiple third-level scale structures arranged along the second direction. The first direction and the second direction are parallel to the surface of the substrate, and the first direction and the second direction are perpendicular to each other. In any group of groove groups, the third-level scale structures are arranged in a line, which is more convenient for femtosecond laser processing. When the laser line scanning operation is performed on the two-scale sample, the processing parameters are a power of 10mW and a line scanning speed of 0.008m / s. The laser line scanning operation directly processes multiple third-level scale structures arranged along the second direction on the surface of the two-scale structure sample.
[0031] When processing the third-level scale structure, it should be noted that the depth of the third-level scale structure is between 50 nanometers and 100 nanometers.
[0032] The metal template can be made of aluminum alloy sheet or other usable templates. PDMS material generally needs to be prepared in advance, and the preparation steps include: uniformly mixing PDMS, ethyl orthosilicate, and dibutyltin dilaurate in a mass ratio of 100:10:1 to obtain PDMS material. In addition, when pouring PDMS material onto the metal template, it is necessary to first spray a layer of PDMS release agent onto the metal template to facilitate demolding.
[0033] While waiting for the PDMS material to solidify, the metal template cast with the PDMS material can be placed in a forced air drying oven at 60 degrees Celsius for curing for 24 hours. After the PDMS material is solidified, it can be peeled off the metal template to obtain a two-scale structure sample.
[0034] Some flexible three-dimensional super-hydrophobic samples were prepared using the preparation method provided in the examples of the present application, and the surface morphology of the obtained samples was comprehensively characterized. The wettability, droplet impact characteristics, droplet freezing characteristics, ice adhesion strength and other properties of the obtained samples were comprehensively tested. In addition, a comparative ratio was set for comparison. The specific process is as follows: First, the smooth aluminum alloy sheet was laser processed by femtosecond laser processing. Multiple aluminum alloy sheets were processed, and rectangular micro-pit array structures with different side lengths were processed on different aluminum alloy sheets. The side lengths of the rectangular micro-pits were 60 , 80 , 100 , 120 and 140 , and then process the aluminum alloy sheet with a diameter of about 10 , with a depth of about 15 , the spacing is approximately The processed aluminum alloy sheet is defined as a two-scale template structure, and the corresponding two-scale template structures are named Al-60, Al-80, Al-100, Al-120, and Al-140 according to the size of the rectangular micro-pits.
[0035] Figures 2 to 6 The real object and optical microscope photos of the two-scale structure template are shown. The left side of the figure is the real object, and the right side is the optical microscope photo. From the optical microscope photos, it can be seen that all templates have obvious first-level scale groove structure and second-level scale groove structure. Obvious submillimeter rectangular micro-pits can be observed. Uniformly distributed second-level scale groove structures can be observed on the surface of the aluminum alloy sheet and inside the submillimeter rectangular micro-pits, that is, the diameter of the groove is 10 Comparing the changes from Al-60 to Al-140, as the size of the first-level groove structure becomes larger, some regular microstructures can be gradually observed in the macroscopic photos. From the optical microscope photos, it can be clearly seen that the side lengths of the rectangular micropits of the Al-60 to Al-140 templates are 60 , 80 , 100 , 120 and 140 , showing an obvious trend of lengthening.
[0036] After the aluminum alloy sheet was transferred using PDMS material, the two-scale structure samples were demolded and named D-60, D-80, D-100, D-120, and D-140 according to the size of the rectangular micro-pits. Figure 7 As shown, Figure 7 The morphology of the two-scale structure samples of D-60 to D-140 is shown in the figure, where (a) corresponds to D-60, (b) corresponds to D-80, (c) corresponds to D-100, (d) corresponds to D-120, and (e) corresponds to D-140.
[0037] Laser scanning was performed on the two-scale structure sample to obtain a flexible three-scale super-hydrophobic surface. The corresponding flexible three-scale super-hydrophobic surfaces were named T-60, T-80, T-100, T-120, and T-140 according to the size of the rectangular micro-pits. In addition, the substrate without the first-level and second-level scale structures but only with the third-level scale structure was named T-0, that is, T-0 was obtained after line scanning the smooth PDMS material surface. Figure 8 As shown, Figure 8The sample morphologies of T-0, T-60, T-80, T-100, T-120 and T-140 are shown in the figure, where (a) corresponds to T-0, (b) corresponds to T-60, (c) corresponds to T-80, (d) corresponds to T-100, (e) corresponds to T-120, and (f) corresponds to T-140. Figure 7 and Figure 8 ,It can be clearly seen that the structure of the sample surface has been enriched and the roughness has been greatly improved after line scanning.
[0038] refer to Fig. 9 As shown, the wettability tests were conducted on T-0, T-60, T-80, T-100, T-120 and T-140, where (a) corresponds to T-0, with a contact angle of 132.4°, (b) corresponds to T-60, with a contact angle of 153.8°, (c) corresponds to T-80, with a contact angle of 162.3°, (d) corresponds to T-100, with a contact angle of 157.6°, (e) corresponds to T-120, with a contact angle of 155.2°, and (f) corresponds to T-140, with a contact angle of 150.1°. Except for T-0, the contact angles of the remaining samples are all greater than 150°, reaching the super-hydrophobic level.
[0039] Droplet impact experiments were conducted on T-0, T-60, T-80, T-100, T-120 and T-140. Fig.10 The results of the droplet impact experiment are shown in Figure 2. Fig.10 It can be clearly seen that compared with T-0, T-60, T-80, T-100, T-120 and T-140 have more obvious rebound effects on water droplets. Water droplets even bounce back and then jump up again on T-60, T-80, T-100 and T-120. The three-scale super-hydrophobic surface with surface flexibility shows low adhesion characteristics to water droplets, especially the water droplets on the surface of T-80 have the highest rebound height, indicating that T-80 has the best water-repellent adhesion effect.
[0040] Droplet freezing experiments were conducted on T-0, T-60, T-80, T-100, T-120 and T-140. Fig.11The results of the droplet freezing experiment show that when the droplets present the same freezing state, different samples require different times. The complete freezing time of the droplets at T-0, T-60, T-80, T-100, T-120 and T-140 is 807s, 931s, 1168s, 1092s, 1033s and 941s respectively. The droplets freeze faster on the T-0 surface, and the freezing time on the flexible three-scale super-hydrophobic surface is significantly delayed, among which the delay effect of T-80 is the most significant. The main reason for the delay in freezing is that the contact angle of the flexible three-scale super-hydrophobic surface is large. The increase in the contact angle makes the contact area between the droplet and the surface smaller, and a large number of bubbles are mixed between the droplet and the three-scale micro-nano structure of the surface, which further slows down the heat transfer.
[0041] The substrate without the first-level scale structure, the second-level scale structure and the third-level scale structure is named D-0, that is, the smooth PDMS material without line scanning is named D-0. The ice adhesion strength of D-0, D-60, D-80, D-100, D-120, D-140, T-0, T-60, T-80, T-100, T-120 and T-140 was tested using an ice strength adhesion device. The test results can be referred to Fig.12 shown.
[0042] The ice adhesion strengths of D-0, D-60, D-80, D-100, D-120, and D-140 are 53.8 kPa, 120.6 kPa, 74.4 kPa, 98.2 kPa, 118.6 kPa, and 135.6 kPa, respectively. The ice adhesion strengths of T-0, T-60, T-80, T-100, T-120, and T-140 are 81.7 kPa, 34.2 kPa, 17.9 kPa, 28.6 kPa, 30.5 kPa, and 42.5 kPa, respectively.
[0043] By comparison, it can be found that the ice adhesion strength of the two-scale structure sample is higher than that of the smooth sample, mainly because water presents a Wenzel state on the two-scale structure surface, and ice forms Wenezel ice. The ice forms a mechanical interlocking state with the surface microstructure, making the ice layer more difficult to remove, that is, the ice adhesion strength is enhanced. As the contact angle increases, it gradually changes from the Wenzel state to the Cassie-Baxter state, and the ice forms Cassie ice. A large amount of air is filled inside the micro-nano structure, making the ice layer easier to fall off, that is, the ice adhesion strength is reduced, so the ice adhesion strength of the three-scale structure samples is relatively low.
[0044] Fig.13The ice adhesion strength on the two-scale and three-scale structures at a wind speed of 5 m / s is shown. The change trend is similar to that of the static ice adhesion strength, but the value has increased. This is mainly because a certain wind speed makes it easier for droplets to adhere to the surface and ice is easier to embed into the surface structure, resulting in an increase in ice adhesion strength. In addition, although the ice adhesion strength on the three-scale structure surface has increased, some of its values are still lower than those on the smooth surface, indicating that the three-scale structure still maintains a certain anti-icing effect.
[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A flexible three-scale super-hydrophobic surface, characterized in that: The invention comprises a substrate, which is a flexible structure, and a plurality of uniformly distributed first-level scale structures, a plurality of uniformly distributed second-level scale structures and a plurality of third-level scale structures are arranged on the surface of the substrate, the first-level scale structure and the second-level scale structure are convex structures, the width dimension of the first-level scale structure is between 60 microns and 140 microns, the width dimension of the second-level scale structure is between 10 microns and 15 microns, the third-level scale structure is a groove structure, the width dimension of the third-level scale structure is between 50 nanometers and 100 nanometers, and the third-level scale structure is arranged on the surface of both the first-level scale structure and the surface of the second-level scale structure.
2. A flexible three-scale super-hydrophobic surface according to claim 1, characterized in that: All the third-level scale structures on the substrate are divided into multiple groups of groove groups arranged along a first direction, each group of the groove groups includes multiple third-level scale structures arranged along a second direction, the first direction and the second direction are parallel to the surface of the substrate, and the first direction and the second direction are perpendicular to each other.
3. A flexible three-scale super-hydrophobic surface according to claim 1, characterized in that: The first-level scale structure is a rectangular protrusion, and the second-level scale structure is a circular protrusion.
4. The flexible three-scale super-hydrophobic surface according to claim 1, characterized in that: The distance between two adjacent second-level scale structures is between 10 microns and 15 microns.
5. The flexible three-scale super-hydrophobic surface according to claim 1, characterized in that: The height of the first-level scale structure is between 80 micrometers and 100 micrometers, the height of the second-level scale structure is between 12 micrometers and 18 micrometers, and the depth of the third-level scale structure is between 50 nanometers and 100 nanometers.
6. A method for preparing a flexible three-dimensional super-hydrophobic surface, for preparing the flexible three-dimensional super-hydrophobic surface according to any one of claims 1 to 5, wherein the specific preparation steps are as follows: Processing a first-level scale groove structure and a second-level scale groove structure on a metal template; Casting a PDMS material on a metal template, and after the PDMS material is solidified, removing the PDMS material from the metal template to obtain a two-scale structure sample having the first-level scale structure and the second-level scale structure; A third-scale structure is processed on the surface of the two-scale structure sample to obtain a flexible three-scale super-hydrophobic surface.
7. The method for preparing a flexible three-dimensional super-hydrophobic surface according to claim 6, characterized in that: The first-level scale groove structure adopts a laser circle drawing and line sweeping processing method, the second-level scale groove structure adopts a laser pulse dot processing method, and the third-level scale structure adopts a laser line sweeping processing method.
8. The method for preparing a flexible three-dimensional super-hydrophobic surface according to claim 6, characterized in that: The metal template is an aluminum alloy sheet.
9. The method for preparing a flexible three-dimensional super-hydrophobic surface according to claim 6, characterized in that: The preparation of the PDMS material comprises: uniformly mixing PDMS, tetraethyl orthosilicate and dibutyltin dilaurate in a mass ratio of 100:10:1 to obtain the PDMS material.
10. The method for preparing a flexible three-dimensional super-hydrophobic surface according to claim 6, characterized in that: The curing process of the PDMS material includes: placing the metal template cast with the PDMS material in a forced air drying oven at a temperature of 60 degrees Celsius for curing for 24 hours.